Penguatan Kapasitas SDM Masyarakat Desa dalam Pengelolaan Sampah Melalui Inovasi Teknologi Konversi Sampah Plastik Menjadi Bahan Bakar untuk Mendukung Ekonomi Sirkular di Kabupaten Grobogan - Arif Surono; Joko Mulyono; Wahyu Wijaya Widiyanto; Marjono, Marjono (Journal of Community Service and Engagement, 2026)
This study analyzes the strengthening of community human resource capacity in rural waste management through the application of plastic waste conversion technology to support the transition toward a circular economy in Grobogan Regency. The program integrated educational interventions, technical demonstrations of pyrolysis-based systems, and institutional facilitation to enhance sustainable waste governance at the village level. Empirical findings indicate increased community understanding of circular economy principles, improved technical knowledge of plastic-to-fuel conversion processes, and greater willingness to participate in technology-based waste management practices. The intervention also encouraged the formation of community waste management groups and strengthened local government support for program sustainability. Behavioral shifts were reflected in the changing perception of plastic waste from environmental burden to economically valuable resource. These outcomes demonstrate that participatory technology adoption can enhance institutional readiness and support decentralized waste-to-energy implementation in rural communities.